Family Laws in the European Union - Monedero, Pablo José Abascal (Socialinė teorija, empirija, politika ir praktika, 2019)
EU social policies should be complemented by contributing to a harmonious development of society, by reducing structural and regional imbalances, developing a balance between the a localized community and the national society, and improving the living standards of citizens and families of member states (Garrido 2002). Such important social policy principles as freedom and justice are addressed and represented in family laws in the EU regulations introduced during the period of 2000–2016. In this article, we studied the EU’s legal solutions in reference to national (Spain) laws on these matters: children and parental responsibility (adoption, child abduction, family benefits) and couples (matrimonial, regimes, prenuptial agreements, provisional measures). This legislation is necessary in the face of the proliferation of families whose members have different nationalities, and even in the mobilization of residences. Cooperation has intensified between national judicial authorities to ensure that legal decisions taken in one EU country are recognized and implemented in any other. This is highly important in civil cases, such as divorce, child custody, maintenance claims, or even bankruptcy and unpaid bills, when the individuals involved live in different countries. The development of family laws is one of the most important factors of family welfare in European countries.
Keywords: family law; European jurisdiction; parental responsibility; adoption; child abduction; matrimonial regimes; prenuptial agreements